Hemodynamic and stress response after sound intervention with different headphone systems: a double-blind randomized study in healthy volunteers working in the health care sector - Hohneck, Anna; Hofheinz, Christina; Usselmann, Rimma; Heinemann, Lara; Weingärtner, Simone; Reckling, Hardy; Schumacher, Gerhard; Burkholder, Iris; Merx, Kirsten; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (Journal of integrative and complementary medicine, 2024)
Objectives: Two headphone systems using different sound systems were compared to investigate the effects of a sound intervention on cardiovascular parameters, indicators of stress, and subjective feelings. - Methods: One hundred volunteers who work in the health care sector reporting elevated workplace-related stress were enrolled and randomized to a 12-min sound intervention (classical music) with either conventional headphones (“MEZE 99 Classic”) or with the same ‒ but internally modified ‒ headphone (called “Lautsaenger”). Cardiovascular parameters were measured with the VascAssist2.0, both before and after sound interventions. In addition, participants were asked to complete questionnaires on burnout risk and emotions/stress. - Results: The study population consisted mainly of female participants (n = 83), with the majority being students (42%). Median age was 32.5 years (range 21-71). In terms of cardiovascular parameters, a significant reduction in aortic pulse wave velocity, as measure of arterial stiffness, and heart rate was observed within both treatment arms. Both systolic blood pressure and arterial flow resistance were reduced by sound intervention, while these effects were only documented with Lautsaenger. Treatment groups were comparable in terms of subjective feedback by participants: a significant increase in emotional wellbeing was achieved with both headphone systems. - Conclusions: A single short-term sound intervention seems to be able to achieve objective cardiovascular improvements in healthy volunteers reporting subjective symptoms of workplace-related stress, using two different headphone systems. Moreover, significant emotional improvement was reported within both arms. - Trial Registration: ISRCTN registry 70947363, date of registration August 13, 2021.